Experimental methods for determining the characteristic quantities of unconventional naval propellers - Nita, C. M; Bocanete, P; Scurtu, I. C (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Basin research involves the practical realization of the scale structure and the analysis of the results according to the studied models and working frequency. The obtained measurements are close in value to those of the numerical simulations, this confirming the numerical results obtained with Ansys Fluent. The analysis carried out on the non-conventional naval propulsion includes all the calculation elements to be able to expand the understanding of this type of propulsion to be able to find the most suitable ones for use in the naval field and not only. The research carried out in this paper presents numerous elements of analysis of the unconventional naval propulsion system. By plotting and validating the thrust functions for a blade, a complete analysis of how this propulsion works is achieved.